The Prevalence of Pathogenic Bacteria from Different Clinical Samples, Northern Part of Iraq - Allaa M. Ahmed (Institute of Medico-legal Publications Pvt Ltd, 2020)
Background : Bacteria are prokaryotic which causes a wide range of diseases in human and animals as well,thus, early diagnosis of bacterial infection is an important step for their management. The vast majority ofbacteria are harmless to human and some strains are even beneficial. However, some strains cause infectionsincluding pneumonia, meningitis and urinary tract infection…etc. The present study aimed to describe anddetermine the prevalence rate of pathogenic bacteria in different clinical samples from Duhok city,Kurdistan region of Iraq, as there are no available data of bacterial infections.Methods: Totally, 200 adult patients enrolled in the present study during July 2017-July 2018. We collecteddifferent clinical specimens including (SFA, Bronchial Lavage, catheter, cerebrospinal fluid, body fluids,blood, semen, stool pus, urine, sputum and ear swabs). Standard microbiological techniques used forisolation and identification. All samples collected before antibiotic uses by specialized physician.Results: The result reported that forty-six samples (23%) obtained from male and one hundred fifty-foursamples (77%) obtained from females. A high diversity of pathogens was found but Staphylococcus aureusrecorded the highest infection rate by (33.3%) which observed in 32 urine samples by and followed by E.coli (27.3%) and Coagulase-Negative Staphylococci (25.3%), which observed in 36 and 29 urine samples,respectively. Alternatively, Klebsiella, Streptococcus, Enterobacteriaceae and Pseudomonas aeruginosawere founded in few samples. Conclusion: The highest diversity of potential pathogens observed in urine samples was E.coi. Over all,Staphlococcus aureus was predominant and recorded the highest prevalence rate by (33.3%) in 50 sampleswhich followed by E. coli recorded in 41 samples (27.3%) and Coagulase-Negative Staphylococci observedin 38 samples (25.3%).